Pengaruh Belanja Modal Pemerintah Daerah Konsolidasian, Indeks Pembangunan Manusia, dan Ukuran Pasar terhadap Investasi Asing di Indonesia - Manggala Adi Windoro; Aditya Ardhi Nugroho; Ingelia Puspita (Jurnal Manajemen Perbendaharaan, 2023)
To respond the challenges of globalization, investment has become one of the driving forces behind economic recovery and sustainable development. Good economic development starts at the regional level. Therefore, the government encourages economic development in regions, including enhancing the investment potential in those areas. In the regional investment climate, foreign direct investment (FDI) plays a crucial role due to its larger investment value compared to domestic investment. However, FDI realization tends to be more volatile, so regional governments need to take strategic measures to manage the investment climate in order to attract foreign investors. This research analyzes several factors that influence foreign inflows in regions. The study employs a panel data estimation model for 34 provinces in Indonesia from 2012 to 2021. The estimation results indicate that consolidated regional government capital expenditure and market size significantly affect foreign inflows in regions, while the Human Development Index does not have an influence.